Challenges in the Management and Conservation of Contemporary Heritage: The Ruins of Villa San Luis de Las Condes - Placencia Jiménez, Jorge Fabián (Revista Historia y Patrimonio, 2024)
The declaration of the ruins of Villa San Luis de Las Condes as a historical monument has presented the State with an unprecedented challenge, not only in terms of the effective legal protection of the property but also in its management and valorization as a site of memory. The current legal framework and governmental institutions have proven insufficient to lead the complex, comprehensive, and sustained process of the monument’s patrimonialization. At least three areas of action require further progress: legal, technical, and political-social. The objective of this paper is to examine some of the challenges facing the management and conservation of contemporary heritage through this case, considering its condition as disintegrated heritage and the disputes over memory it has generated. To this end, public policies that have shaped the historical trajectory of Villa San Luis, from its creation to the present, are reviewed; institutional practices related to its management and conservation are problematized from the perspective of critical heritage theory; and some exploratory and open alternatives are proposed to address the challenges posed by the patrimonialization of these ruins.